Second Nature : Poems - Gibson, Margaret, 1944- (Book collections on Project MUSE., 2010)
Learn of the green world what can be thy place," wrote Ezra Pound. In Second Nature, her tenth collection of poems, Margaret Gibson takes Pound=s stern counsel to heart. With stunning clarity, these poems move from acute observation to an empathy, participation, and intimacy that continues Gibson=s search to experience the Aone body@ of the world in direct encounter and to translate that encounter into words. As Emerson tells us, the Spirit moves throughout Nature and through usCour art is, therefore, second nature. Whether Gibson=s poems take us to Greece and to Aa writing desk no larger than.